2005
DOI: 10.1007/s10750-005-3620-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Whole-lake, Experimental Fertilization on Lake Trout in a Small Oligotrophic Arctic Lake

Abstract: We tested whether increased phosphorus and nitrogen concentrations would affect a lake trout (Salvelinus namaycush) population in a small oligotrophic lake with a benthically dominated food web. From 1990 to 1994, nitrogen and phosphorus were added to Lake N1 (4.4 ha) at the arctic Long-Term Ecological Research site in Alaska. We used mark/recapture methods to determine the lake trout population size, size structure, recruitment, and individual growth from 1987 to 1999. Data were also collected on water chemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 75 publications
2
17
1
Order By: Relevance
“…Abundance of adult lake trout more than doubled during aquaculture, accompanied by increased growth rates, maturation at earlier ages and larger sizes and improved body condition, probably in response to increased prey availability (Kennedy et al., In press) facilitated by increased nutrient loading (Bristow et al., ). Increased growth rates of lake trout in response to nutrient enrichment has been reported elsewhere (Lienesch et al., ). Recent work demonstrated that increased size at age reported here correspond well with back‐calculated size at age in Lake 375, which was based on a greater number of observations and arguably better reflect true early growth patterns in the lake (Kennedy et al., In press).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Abundance of adult lake trout more than doubled during aquaculture, accompanied by increased growth rates, maturation at earlier ages and larger sizes and improved body condition, probably in response to increased prey availability (Kennedy et al., In press) facilitated by increased nutrient loading (Bristow et al., ). Increased growth rates of lake trout in response to nutrient enrichment has been reported elsewhere (Lienesch et al., ). Recent work demonstrated that increased size at age reported here correspond well with back‐calculated size at age in Lake 375, which was based on a greater number of observations and arguably better reflect true early growth patterns in the lake (Kennedy et al., In press).…”
Section: Discussionsupporting
confidence: 62%
“…Abundance of adult lake trout more than doubled during aquaculture, accompanied by increased growth rates, maturation at earlier ages and larger sizes and improved body condition, probably in response to increased prey availability (Kennedy et al, In press) facilitated by increased nutrient loading (Bristow et al, 2008). Increased growth rates of lake trout in response to nutrient enrichment has been reported elsewhere (Lienesch et al, 2005).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It was surmised that the relatively high length and age-specific fecundity in Swan Lake further indicated that resources were not limiting adult lake trout. Somatic growth varies widely among lake trout populations throughout their geographical range in relation to lake productivity and food web structure (Trippel 1993;Shuter et al 1998;Johnson & Martinez 2000;Lienesch et al 2005;McDermid et al 2010). Lake trout generally grow faster and attain larger sizes in lakes with high productivity and pelagic forage species (Martin & Olver 1980;Shuter et al 1998;McDermid et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Lake trout thrive in deep, well-oxygenated lakes and are sensitive to the effects of eutrophication (Evans et al 1996;Evans 2007;Gunn et al 2004). Previous fertilization experiments revealed lake trout growth and recruitment increased following nutrient enrichment, but prolonged eutrophication-induced hypoxia may cause declines in lake trout recruitment over time (Lienesch et al 2005). There remains considerable uncertainty around how changes in community dynamics of lake ecosystems with eutrophication influence lake trout early growth, condition, and resource use.…”
Section: Introductionmentioning
confidence: 99%